Metataxonomic and metabolomic evidence of biofilm homeostasis disruption related to caries: An in vitro study. (19th February 2022) - Sánchez, María C.; Velapatiño, Angela; Llama‐Palacios, Arancha; Valdés, Alberto; Cifuentes, Alejandro; Ciudad, María J.; Collado, Luis
Abstract: The ecological dysbiosis of a biofilm includes not only bacterial changes but also changes in their metabolism. Related to oral biofilms, changes in metabolic activity are crucial endpoint, linked directly to the pathogenicity of oral diseases. Despite the advances in caries research, detailed microbial and metabolomic etiology is yet to be fully clarified. To advance this knowledge, a meta‐taxonomic approach based on 16S rRNA gene sequencing and an untargeted metabolomic approach based on an ultra‐high performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry analysis (UHPLC/Q‐TOF‐MS) were conducted. To this end, an in vitro biofilm model derived from the saliva of healthy participants were developed, under commensal and cariogenic conditions by adding sucrose as the disease trigger. The cariogenic biofilms showed a significant increase of Firmicutes phyla ( p  = 0.019), due to the significant increase in the genus Streptococcus ( p  = 0.010), and Fusobacter ( p  < 0.001), by increase Fusobacterium ( p  < 0.001) and Sphingomonas ( p  = 0.024), while suffered a decrease in Actinobacteria ( p  < 0.001). As a consequence of the shift in microbiota composition, significant extracellular metabolomics changes were detected, showed 59 metabolites of the 120 identified significantly different in terms of relative abundance between the cariogenic/commensal biofilms (Rate of change > 2 and FDR < 0.05). Forty‐two metabolites were significantly higher in abundance in the cariogenic biofilms, whereas 17 metabolites were associated significantly with the commensal biofilms, principally related protein metabolism, with peptides and amino acids as protagonists, latter represented by histidine, arginine, l ‐methionine, glutamic acid, and phenylalanine derivatives.